All you can eat: greed, lust, and the new capitalism - McQuaig, Linda (Penguin, 2001)
Explains the mired history of social and economic thinking that has culminated in the new capitalism. McQuaig argues that instead of shaping our society to fit the economy, we must shape the economy to fit the society we want. 2001.
Economics
Keywords: business & economics; capitalism; capitalism - history; economic history; free enterprise; political science

Constructing a European Market: Standards, Regulation, and Governance - Egan, Michelle P. (Oxford University Press, 2001)
'An excellent contribution to our understanding of the political construction of markets... This is a well-written book, enjoyable to read as well as being very informative. I view this volume as a 'must read' for all scholars and graduate students in the areas of government and business, the politics of market economies and comparative politics in general. Michelle Egan's description and explanation of market construction and its impact on business standards, regulation and governance will be valuable to all of us for many, many years to come.' -Henry Jacek, McMaster University; Polibus: Newsletter of the IPSA Research CommitteeThis book provides a detailed analysis of the policies and institutions used by the EU to create a single market. Through a historical overview, sectoral case studies, and an assessment of recent policy initiatives, the author provides a comprehensive account of the evolution of European economic integration.
Political Science; Economics
Keywords: European Court of Justice; European Union; United States; business & economics; economic policy; harmonization; market integration; mutual recognition; public policy; regulation; single market; standards; trade barriers